Penglibatan orang Cina dalam industri penghasilan makanan di Butterworth, 1957-2000 - Tan, Soon Chin (Tanjong Malim, 2018)
Penglibatan orang Cina dalam industri penghasilan makanan di Butterworth, 1957-2000 by Tan, Soon Chin